Analysis Of Transnational Organized Crime Activities in West Sulawesi Adolescent Case: Drugs Trafficking in Fringe Community - Gia Ayu Fita; Wandi Abbas (Indonesia Prime, 2021)
Changes resulting from globalization based on information systems and technology that very fast make countries seem borderless. Not only related to the country's economic growth, but the development of globalization also impacts transnational criminal activities that have experienced significant growth in various parts of the world. Countries with lower levels of national security have greater difficulties in dealing with the globalization of crime. Weaknesses and vulnerabilities in the security sector are the main reasons the country is increasingly becoming a stage for transnational organized crime, especially drug trafficking. The movement towards drug trafficking activities in Indonesia has targeted urban areas and has also taken root in fringe communities such as in the province of West Sulawesi. The target of drug trafficking activities has also targeted adults and teenagers. It is evident from the increasing number of cases of drug users among teenagers in West Sulawesi, which occupies the 18th position out of 34 provinces in Indonesia. In this study, the analysis will be carried out on the drug trafficking movement among adolescents in West Sulawesi, which will later produce a guideline that can be used as reference material by various parties. With this case, the local government and stakeholders regarding handling drug trafficking cases among adolescents in West Sulawesi